Towards an understanding of the ethics of electronic consent in clinical trials - Sahan, K; Wijesurendra, R; Preiss, D; Mafham, M; Sheehan, M (BioMed Central, 2024)
There are good practical reasons to use electronic consent (e-consent) in randomised trials, especially when conducting large-scale clinical trials to answer population-level health research questions. However, determining ethical reasons for e-consent is not so clear and depends on a proper understanding of what e-consent means when used in clinical trials and its ethical significance. Here we focus on four features of ethical significance which give rise to a range of ethical considerations relating to e-consent and merit further focused ethics research.